The Impact of Governance Principles on Institutional Performance in Riyadh's Engineering Sector: A Mixed-Methods Analysis - Higazey, Mohammed (LPPM Universitas Jambi, 2025)
This study investigates the impact of governance principles (rule of law, transparency, accountability, participation, and strategic vision) on enhancing organizational performance in Riyadh's engineering sector, focusing on effectiveness, efficiency, and productivity. Using a descriptive-analytical method, data were analyzed to identify ways to improve the current situation. The sample included employees with professional management certifications, specifically from the Project Management Institute (PMI). A questionnaire with 33 items was distributed, yielding 360 valid responses analyzed using SPSS software. Results indicated a statistically significant impact (α ≤ 0.05) of governance principles on organizational performance. Specifically, 82.3% of the variation in performance could be explained by governance dimensions. Participants agreed on the importance of governance implementation in the engineering sector, with a relative weight of 78.4%, and similarly rated organizational performance at 77.8%. Among the governance principles, the rule of law ranked highest in influence, followed by transparency, strategic vision, and accountability, while participation had the least impact. The novelty of this research lies in its focus on a rarely studied sector in Saudi Arabia, using certified professionals as a sample, offering empirically grounded insights into governance-performance links. The study's practical contributions include clear recommendations for developing governance training, establishing monitoring units, and improving awareness through professional bodies to support sustainable organizational improvement.